Urban micro-forestry for climate adaptation in the smaller ports of the mid-Adriatic sea - Roberta Cocci Grifoni; Timothy D. Brownlee; Graziano Enzo Marchesani; Maria Federica Ottone (Agathón)
The article describes a research work aimed at identifying tools to support the activation and environmental regeneration of the open space of the ports in the mid-Adriatic area, an area with untapped potential, though there are significant criticalities. Starting from a set of data taken from the INTERREG Italy-Croatia Joint_SECAP project and, in particular, from the risks and climatic vulnerabilities of the Italian mid-Adriatic city, the contribution presents hypotheses for the light transformation of a part of the port infrastructure through urban micro-forestry interventions. The methodological approach uses simulation tools with a parametric platform that generates proprietary algorithms and allows recursive control over every aspect of the process.